Monetary Policy under Zero Reserve Requirement in Canada - Akhsyim Afandi (Economic Journal of Emerging Markets, 1997)
Current development shows that financial system tends to move to the direction where controls over banking system would be very minimum. Banks are no longer required to hold afraction of their assets as required reserve with the central bank, and deposits are not subject to interest rate regulation. Fama (1980, 1983) argues that with the absence of reserve ratio price determinacy still holds through the control over currency supply. However, recent development also indicates that the control over currency supply is not any more in the hand of central banks but determined by the demand of the people. Consequently, price level is uncontrollable. Black (1970) even goes further to conclude that the unregulated banking system will bring the traditional monetary theories to an end. This paper deals with the implications of recent development in financial system in Canada. This paper argues that even though there is no longer reserve requirement and currency supply is determined by demand side, the Bank of Canada still has control over nominal magnitude of the economy, namely interest rates, which in turn influence aggregate demand and prices.